THE IMPACT OF PEACE BUILDING IN THE TRANSITIONAL SOCIETY - Alier, Dr. Gabriel; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
Peace is the presence of justice and peace building entails addressing all factors and forces that stand as impediments to the realization of all human rights for all human beings. Canadian Peacebuilding Initiative of the Department of Foreign Affairs and International Trade (DFAIT) and the Canadian International Development Agency (CIDA) provides a definition of peacebuilding in its Strategic Framework: as the effort to strengthen the prospects for internal peace and decrease the likelihood of violent conflict (CIDA, 2012). The over-arching goal of peacebuilding is to enhance the indigenous capacity of a society to manage conflict without violence (Castillo, 2008). Peace Building is the presence of justice and peace building entails addressing all factors and forces that stand as impediments to the realization of all human rights for all human beings. Canadian nation building Initiative of the Department of Foreign Affairs and International Trade (DFAIT) and the Canadian International Development Agency (CIDA) provides a definition of nation building in its Strategic Framework: as the effort to strengthen the prospects for internal peace and decrease the likelihood of violent conflict (CIDA, 2012). The over-arching goal of peace building is to enhance the indigenous capacity of a society to manage conflict without violence (Castillo, 2008). Ultimately, peace building aims at building human security, a concept which includes democratic governance, human rights, rule of law, sustainable development, equitable access to resources, and environmental security (Cotet and Tsui, 2013). Peace building may involve conflict prevention, conflict resolution, as well as various kinds of post-conflict activities. It focuses on the political and socio-economic context of conflict, rather than on the military or humanitarian aspects. It seeks to address this challenge by finding means to institutionalize the peaceful resolution of conflicts (OECD, 2009). During the post-conflict Nation building phase, the challenges can best be captured along three broad themes: security, welfare and representation (Macrae, ed. 2009). These represent the core functions of the modern state, whether democratic or authoritarian, and are also central to peace building. Before the current concept of ‘stabilization’ came into play, historical and theoretical knowledge considered security concerns – mainly disarmament, demobilization and reintegration (DDR), and security sector reform (SSR)– as the focus of post-conflict peace building and as core functions of a state in post-conflict situations(Lucchi, 2010). However, the current concepts of security and stabilization signal that peace building is not limited to the aftermath of conflicts and can take place at any phase in a ‘fragile state’ situation(Cotet and Tsui, 2013).